Effects of high arsenic and fluoride soil concentrations on soybean plants - Bustingorri, Carolina (2015)
Fil: Bustingorri, Carolina. Universidad de Buenos Aires. Facultad de Agronomía.Instituto de Investigaciones en Biociencias Agrícolas y Ambientales (INBA). Buenos Aires, Argentina.